2000
DOI: 10.1111/j.1745-7599.2000.tb00305.x
|View full text |Cite
|
Sign up to set email alerts
|

Integration of Spirituality into Health Care Practice by Nurse Practitioners

Abstract: Although conceptualizations of mind, body, and spirit are ancient, spiritual aspects have not been readily integrated into health care. Western medicine's mechanistic model, with its "fix-broken-parts" paradigm, focuses on the physical body, with occasional consideration given to emotional and mental aspects. One's view of self in relation to a Supreme Being, and one's existence and purpose for life is central to health at all levels, e.g., spiritual, physical, emotional, and cognitive. The purpose of this art… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0
4

Year Published

2002
2002
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 24 publications
1
20
0
4
Order By: Relevance
“…Our study identified that age, religious beliefs, seniority, and childhood spirituality represented the essential factors affecting nurses' spiritual intelligence. Nursing's longstanding tradition of caring inherently places nurses in an ideal position to act as role models for health care professionals in integrating spirituality into health care practice (Treloar, 2000). The experience of spiritual well-being may predict a positive attitude on the part of a nurse toward spiritual care, and thus influence the overall ability to assist patients to overcome their spiritual distress (Narayanasamy & Owens, 2001).…”
Section: Resultsmentioning
confidence: 99%
“…Our study identified that age, religious beliefs, seniority, and childhood spirituality represented the essential factors affecting nurses' spiritual intelligence. Nursing's longstanding tradition of caring inherently places nurses in an ideal position to act as role models for health care professionals in integrating spirituality into health care practice (Treloar, 2000). The experience of spiritual well-being may predict a positive attitude on the part of a nurse toward spiritual care, and thus influence the overall ability to assist patients to overcome their spiritual distress (Narayanasamy & Owens, 2001).…”
Section: Resultsmentioning
confidence: 99%
“…Despite increased efforts to integrate holism into health care, many helping professionals ignore spiritual issues surrounding disability. In the midst of theological confusion surrounding the meaning of disability, public attitudes for disability, and limited integration of spirituality into health care (Treloar 2000), people with disabilities may internalize negative messages that contribute to rejection of God and spiritual beliefs that could be helpful.…”
Section: Spirituality and Healthmentioning
confidence: 99%
“…Listening and providing respect, along with simply being present, seem to be the essence of spiritual care. 9 ,10,19 In addition, Treloar 20 stated that the ultimate purpose of spiritual care (in nursing) is not to solve the patient's spiritual problems but to create an environment and provide resources conducive to spiritual expression and healing by the patient and his or her family. As such, a better understanding of the practice of spirituality as it relates to patient care might avert some of the apparent reluctance by ATs to agree that they should do it.…”
Section: Discussionmentioning
confidence: 99%